Biological control of three floating water weeds, Eichhornia crassipes, Pistia stratiotes, and Salvinia molesta in the Republic of Congo - Mbati, G.; Neuenschwander, Peter (Springer, 2005)
Since 1999, four specific weevils (Coleoptera, Curculionidae) were released in the Republic of Congo against three exotic floating water weeds: Neochetina eichhorniae Warner and N. bruchi Hustache against water hyacinth, Neohydronomus affinis Hustache against water lettuce, and Cyrtobagous salviniae Calder and Sands against water fern. Recoveries of exotic weevils were made from all 24 release sites except one, and all four species have established and spread (up to 800 km for water hyacinth weevils). Within a few years of releases, control of water fern and water lettuce was such that fishing and navigation could be resumed, while reductions of water hyacinth populations were only beginning.